Predation Intensity on the Brittle Star Ophiomastix annulosa on Serinting Beach of Lombok Island - Al-Khulaifi, Fazza Firjatullah; Bachtiar, Imam; Khairuddin, Khairuddin; Suyantri, Eni (Jurnal Biologi Tropis, 2024)
The Ophiuroid has an important role in intertidal area. Many scientific papers show predation (partial loss of arms) on Ophiuroid. Predators of the Ophiuroid include sea urchins, sea stars, demersal fish, shrimp, and crabs. Ophiuroid that have a larger disc diameter can prey on species that have a smaller disc diameter. This study aims to describe the predation intensity of the Ophiomastix annulosa using the cruising method and analyze the correlation between disc diameter and predation intensity at the Serinting Beach, Special Economic Zone (SEZ) of Mandalika. The results showed that disc diameter and predation intensity on O. annulosa varied greatly. The size of the disc diameter found ranged from 1.01-2.55 cm. Most disc diameters were found at 1.55-1.84 cm. A total of 45% of the sample brittle star experienced predation. Predation intensity was mostly found at loosing one arm. There was no correlation between O. annulosa disc diameter and predation intensity at Serinting Beach Mandalika.